Pengaruh Suhu Dan Lama Penyimpanan Pada Kualitas Fisik Dan Mikrobiologis Telur Ayam Ras - Putri Trinitariyani; Aji Winarso; Annytha I.R Detha (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Eggs are one of the products from animals that are most widely used by the community, eggs have a fairly complete nutritional content and also the price is relatively cheap. Egg quality can decrease. Temperature and length of storage of eggs can affect egg quality. The purpose of this study was to determine the effect of different temperatures and storage periods on and determine the optimal egg quality and microbiology of eggs laying hens at different temperatures and storage periods. This research was conducted by using a sample of eggs laying hens aged 0 days and getting treatment by being stored in different storage conditions. Parameters measured to determine egg quality were organoleptic, egg white index, egg yolk index, Haugh Unit, pH and microbiological quality. This study was a completely randomized design (CRD), which consisted of six treatments with three trials. Based on the tests that have been carried out, the Haugh Unit, Egg White Index, Egg Yolk Index, Organoleptic and Total Plate Count values of eggs stored at room temperature and 4 °C have an influence on egg quality. purebred eggs laying hens stored at 4 °C have better quality in terms of shelf life compared to eggs stored at room temperature.